Alkaptonuria - Case report - Fernanda Helena Craide; Juliana Salvini Barbosa Martins da Fonseca; Priscila Coelho Mariano; Natalia Monteiro Fernandez; Carlos Gustavo Carneiro de Castro; Yuri de Souza Lima Mene (Sociedade Brasileira de Dermatologia, 2014)
Alkaptonuria, also called endogenous ochronosis, is a rare metabolic autosomal recessive disorder. It occurs by complete inhibition of homogentisic acid oxidase enzyme having its deposition in various tissues. Male patient, 52 years old, sought medical help complaining about progressive appearance of hyperchromic papules on the lateral edge of the second finger of both hands for 02 years. He also complained about darkening of urine, sperm and underwear. Incisional biopsy of second hand finger and test for homogentisic acid in the urine results were positive. The findings are compatible with the diagnosis of alkaptonuria. Given these findings, treatment was initiated, followed-up by other specialties and he was advised to avoid certain foods.